Measurement of boundary force and wall friction coefficient during the development of a granular discharge flow from a symmetric silo. (19th May 2021) - Jiang, Ming-Zhe; Tsai, Jih-Chiang; Yang, Fu-Ling
ABSTRACT: Self-developed sensing modules were implemented in a symmetric silo of flat base to study the spatial-temporal evolution of the normal and tangential boundary force from the onset of a granular discharge. The static force profiles can be reproduced by Janssen's model but peculiar variation into non-Janssen force depth profiles was detected after the onset of discharge. Interestingly, the two force components evolved in a consistent manner at steady discharge to yield a narrow range of the effective wall friction coefficient μ w . As for the transient phase before the steady discharge, different transient evolution trends were discovered for μw ( t ) to a value much greater than the value at steady discharge and the type of μw ( t ) evolution is closely tied with the initial static force state.